1986
DOI: 10.1152/jappl.1986.60.5.1542
|View full text |Cite
|
Sign up to set email alerts
|

Human thermoregulatory responses to cold air are altered by repeated cold water immersion

Abstract: The effects of repeated cold water immersion on thermoregulatory responses to cold air were studied in seven males. A cold air stress test (CAST) was performed before and after completion of an acclimation program consisting of daily 90-min cold (18 degrees C) water immersion, repeated 5 times/wk for 5 consecutive wk. The CAST consisted of resting 30 min in a comfortable [24 degrees C, 30% relative humidity (rh)] environment followed by 90 min in cold (5 degrees C, 30% rh) air. Pre- and postacclimation, metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 18 publications
6
82
3
Order By: Relevance
“…Also in agreement with the previous report, Bittel (5) observed that skin temperatures fell more during the coldexposure test after than before acclimation. In contrast to observations of Young et al (68), rectal temperatures did not fall as much during the post-acclimation cold-air exposure as before acclimation, but this may have reflected the warmer air temperature used for the standardized cold-air test. Bittel (5) calculated that the net effect of acclimation was a significant reduction in the heat debt that developed during cold-air exposure.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Also in agreement with the previous report, Bittel (5) observed that skin temperatures fell more during the coldexposure test after than before acclimation. In contrast to observations of Young et al (68), rectal temperatures did not fall as much during the post-acclimation cold-air exposure as before acclimation, but this may have reflected the warmer air temperature used for the standardized cold-air test. Bittel (5) calculated that the net effect of acclimation was a significant reduction in the heat debt that developed during cold-air exposure.…”
contrasting
confidence: 99%
“…Following the eight week program of repeated cold-water immersion, cold-air exposure caused skin temperature to fall about 4 0( lower than before acclimation (68). Although skin blood flow was not actually measured, the greater fall in skin temperature during cold exposure was similar to the adjustments noted by others studying the Central Australian Aborigine, and suggests that a more pronounced cutaneous vasoconstrictor response to cold had developed.…”
Section: Acclimation Induced By Repeated Cold-water Immersionmentioning
confidence: 61%
“…We and others have found that catecholamine neurotransmitter systems in the brain can also be affected by cold stress. Acute cold stress has been shown to increase norepinephrine release (Yeghiayan et al 2001;Young et al 1986), and chronic (2-4 weeks) cold stress exposure has been shown to increase noradrenergic receptor sensitivity, enhance the noradrenergic response to acute stress, and sensitize the acute excitability of noradrenergic neurons in locus coeruleus (Gresch et al 1994;Jedema and Grace 2003;Ma and Morilak 2005;Mana and Grace 1997;Pardon et al 2003). In addition, a variety of stressors, including cold stress, also increase dopamine utilization, leading to a reduction in central levels of both catecholamines (e.g., Dunn and File 1983;Finlay and Zigmond 1997;Reinstein et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mental stress-induced serum NE levels are also higher in SSc patients than in normal individuals based on mental calculation stress tests, suggesting that SSc patients may have an impaired function of the neuro-endocrine-immune system due to stress 1 . Previous findings showed that serum NE levels in normal individuals were increased after cold exposure 2 , and serum NE levels increased after repeated cold-water immersions 3 , further indicate that emotional stress and cold exposure increase the systemic and/or local NE levels in SSc patients.…”
Section: Discussionmentioning
confidence: 78%